2021
DOI: 10.26650/eor.20210033
|View full text |Cite
|
Sign up to set email alerts
|

The in-vitro effects of white henna addition on the candida albicans adhesion and physical properties of denture base resin

Abstract: PurposeThis in-vitro study evaluated and compared the effect of white henna (WH) and natural henna (NH) addition on Candida albicans adhesion and physical properties of the denture base material. Materials and MethodsA total of 243 acrylic resin specimens (9 per group) were divided as follows: 81 for flexural strength, 81 for Candida albicans adherence test, and 81 for surface roughness, translucency, and hardness. Heat-polymerized acrylic resin specimens were prepared by adding 0.5, 1.0, 1.5, or 2.0 wt% of WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This is essential as bioactive resin-based materials must be mechanically stable to avoid any mechanical failure during their clinical service inside the oral cavity. In another investigation, this concern was resolved where the mechanical and antifungal properties of heat-polymerized acrylic resins containing 0.5, 1.0, 1.5, or 2.0 wt.% of white and natural Henna were investigated [ 63 ]. The flexural strength, surface roughness, and translucency values of Henna-containing DBRs were negatively affected by increasing the concentration of white and natural Henna.…”
Section: Methods Used For Tuning Bioactive and Antimicrobial Dbr Mate...mentioning
confidence: 99%
See 2 more Smart Citations
“…This is essential as bioactive resin-based materials must be mechanically stable to avoid any mechanical failure during their clinical service inside the oral cavity. In another investigation, this concern was resolved where the mechanical and antifungal properties of heat-polymerized acrylic resins containing 0.5, 1.0, 1.5, or 2.0 wt.% of white and natural Henna were investigated [ 63 ]. The flexural strength, surface roughness, and translucency values of Henna-containing DBRs were negatively affected by increasing the concentration of white and natural Henna.…”
Section: Methods Used For Tuning Bioactive and Antimicrobial Dbr Mate...mentioning
confidence: 99%
“…Opposite to most of the antimicrobial compounds, increasing the Henna concentrations increased the C. albicans biofilms. Only 0.5 wt.% of white and natural Henna reduced the C. albicans significantly compared to the control with no addition [ 63 ]. This could be attributed to the increased surface roughness associated with the other concentrations, which could facilitate the attachment of C. albicans .…”
Section: Methods Used For Tuning Bioactive and Antimicrobial Dbr Mate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the extracts of L. inermis, particularly its leaves, contain compounds that can inhibit protein glycation by blocking the formation of AGEs or scavenging reactive carbonyl species, which are involved in the glycation process. These compounds may include phenolic compounds, flavonoids, and other bioactive compounds present in L. inermis (163).…”
Section: Protein Glycation Inhibitionmentioning
confidence: 99%